The March of Islam : AD 600-800 - Time-Life Books (Amsterdam : Time-Life Books, 1991)
1. World History--AD 600-800 2. Islam
Includwes bibliographical references.
Bibliography: p. 172-173.
Basic Ed. Students
Keywords: Middle Ages